Female Expatriate Managers - Barriers Experienced and Suggested Strategies - Ali, Syeedun; Farooqui, Rahela (Prabandhan: Indian Journal of Management, 2010)
With the globalization of the world economy, the world is shrinking at a fast pace. The companies are not restricted to one country, but have crossed the boundaries and have a presence in other countries as well. This has led to increase in the multicultural workforce. The one phenomenon which is quite evident due to globalization is the increase in the number of expatriate managers. But if we compare the number of male and female expatriate managers, we will find a striking variation. The increase in number of female expatriates in comparison to their male counterparts is not on the same line. Women face discrimination in the company’s selection policy as companies feel that sending a woman as an expatriate will not be a good business policy. They not only face discrimination in company’s selection policy, but also in their foreign assignments. Women face discrimination that prevents them from getting the international assignments and experience, which is important for the promotion to the top management level. The responsibility to eliminate the discriminations that women face is both with the female managers and the companies. While women in the recent past were able to reduce this discrimination in many developed countries, but studies reveal that companies are still relying more on the male candidates for global assignments.